What makes for a great team? - Hackman, J. Richard (Henry Stewart Talks, 2013)
Team effectiveness, The “leader attribution error”, Conditions for team effectiveness, Real team, Team stability and performance over time, Compelling direction, Specifying means vs. ends, Right people, The greebles experiment, Team performance by condition, The three essentials conditions, Sound structure, Links among members as team size increases, A counterterrorism simulation, Supportive context, Organizational context checklist, Team coaching, The team life cycle, The interaction of team design and coaching, What is a team leader to do?
Reviewed at 2017/02/27